2013
DOI: 10.1148/radiol.13121746
|View full text |Cite
|
Sign up to set email alerts
|

Stage IB1 Cervical Cancer: Role of Preoperative MR Imaging in Selection of Patients for Fertility-Sparing Radical Trachelectomy

Abstract: Pretrachelectomy MR imaging can help identify high-risk patients likely to need radical hysterectomy or confirm the absence of residual tumor in the cervix after a cone biopsy with negative margins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 41 publications
1
65
0
2
Order By: Relevance
“…Therefore, MRI may be an alternative tool for assessing DSI in early-stage cervical cancer. However, the performance of MRI is limited primarily by the difficulty of distinguishing a tumor from post-procedural inflammation, and by the fact that accuracy for detection of DSI might be improved if the MRI were performed before conization [25]. …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, MRI may be an alternative tool for assessing DSI in early-stage cervical cancer. However, the performance of MRI is limited primarily by the difficulty of distinguishing a tumor from post-procedural inflammation, and by the fact that accuracy for detection of DSI might be improved if the MRI were performed before conization [25]. …”
Section: Discussionmentioning
confidence: 99%
“…Preoperative MRI provides useful information on tumor size, parametrial status and lymph nodes, contributing to the more accurate selection of candidates for trachelectomy. Recently, it has been shown that patients with a ≤ 5 mm distance between tumor and ICO on MRI, fare better with radical hysterectomy than trachelectomy [56] . MRI may also be used for monitoring patients after trachelectomy.…”
Section: Trachelectomy Patientsmentioning
confidence: 99%
“…Eligibility requirements include tumor smaller than 2 cm, distance from tumor margin to internal cervical os of more than 1 cm, and absence of lymph node metastases. MR imaging assesses the extent of local tumor with high accuracy (13) and is routinely used for patient selection. 18 F-FDG PET/CT is also used in many institutions to evaluate for lymphadenopathy.…”
mentioning
confidence: 99%